Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru di SMK Al-Falah - Hosiyatun Hotima; Halimatus Sa'diyah (Nusantara Journal of Islamic Studies, 2022)
This study aims to describe the Principal's Leadership in Improving Teacher Performance in Al-Falah Vocational School. The research method uses qualitative research. The informants in this study are school principals and educators or teachers. The key informant is how the principal in supervising and developing teacher performance, either directly or through the Deputy Head of Curriculum. The data collection procedure used three techniques, namely through observation, interviews and documentation studies. For the validity of the data, researchers used triangulation techniques. The results showed that: the principal's leadership in improving teacher performance at SMK Al-Falah was good. Thus, it can be concluded that the principal's leadership contributes well to the advancement of the quality of education where the performance of educators or teachers is the key to success in the world of education.